Evaluation of lower quality recycled PCCP for Portland Cement Treated Base (PCTB) - Daily, Koby Francis (Kansas State University, 2018)
With recycled concrete aggregates (RCA) becoming a more popular and cost effective alternative to virgin aggregate, the Kansas Department of Transportation (KDOT) looks to incorporate these aggregates into Portland cement treated base (PCTB). KDOT currently practices a freeze-thaw method that includes 90 days of curing and a maximum of 660 freeze-thaw cycles to determine the durability of its concrete pavements and bases. An experimental study was conducted to determine if lower quality RCA would be an adequate replacement for virgin aggregates within PCTB. Two sources of D-cracked aggregate from “D” cracked pavements, were acquired and used to batch the PCTB. Control samples were batched using virgin aggregates following the gradation of the two sources of RCA. Following the procedure laid out by KDOT, both the RCA and control samples were tested for durability. The results showed that increasing the total amount of cementitious binder in the PCTB increased the durability. Also at lower binder contents, the type of RCA had an impact on the performance of the base containing RCA. In addition, the RCA and control samples had similar performance, and as a result RCA could be a viable aggregate source for PCTB. Finally, it was determined that different criteria need to be developed for the freeze-thaw durability of PCTB as mass loss was an important factor for PCTB with D-cracked aggregates
Keywords: Base; Civil; Pavement; Daily; KDOTConcrete